A Matemática Via Algoritmo de Criptografia El Gamal - Morais, Glauber Dantas (2013)
The encryption algorithm written by Egyptian Taher ElGamal computes discrete logarithms with elements of a finite group G Cyclical. These elements have properties that during the study Chapter 1. Knowing the definitions and some properties studied, we can define and compute discrete logarithms, using knowledge of arithmetic and congruence of Remains and Theorem Remainder of Chinese. We will study public key algorithms, in particular the algorithm written by ElGamal, seeking to understand the diffculties presented by it and show its applications in the field of cryptography. We present a sequence of activities, aimed at students of the first grade of high school, targeting the learning of some subjects covered at work.